Quality of life and social support as key determinants of anxiety and depression in Myasthenia Gravis: evidence from a Chinese cohort - Li, Xiang; Li, Zhipeng; Zhang, Chaoyue; Li, Long; Liang, Yimin; Zhang, Xuxiang; Liu, Fengbin; Lin, Xinfeng; Jiang, Qilong (Frontiers in Neurology, 2025)
BackgroundMyasthenia Gravis (MG) is a chronic autoimmune disorder frequently accompanied by anxiety and depression, which aggravate disease burden. Evidence on the relationship between clinical characteristics and psychological symptoms in MG remains inconsistent.MethodsWe conducted a cross-sectional study of 93 Chinese MG patients. Clinical and demographic data were collected, and anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). Associations were examined by correlation, chi-square tests, and logistic regression with false discovery rate (FDR) correction. Multivariable models adjusted for age and sex. ROC curve analyses evaluated the predictive performance of (MG Activities of Daily Living) MG-ADL, (15-item Myasthenia Gravis Quality of Life scale) MG-QOL-15, and (Social Support Rating Scale) SSRS.ResultsAnxiety and depression were present in 30.1 and 35.5% of patients, respectively. In multivariable analysis, reduced quality of life (MG-QOL-15, OR = 0.85, 95% CI: 0.78–0.92, p < 0.001) and insufficient social support (SSRS, OR = 1.08, 95% CI: 1.00–1.16, p = 0.03) independently predicted psychological distress, whereas MGFA classification was not significant. Supplementary linear regression confirmed these findings. ROC analysis showed MG-QOL-15 had the best performance in detecting both anxiety (AUC = 0.884) and depression (AUC = 0.837), while SSRS had moderate value and MG-ADL limited discrimination.ConclusionPsychological distress in MG is more closely linked to quality of life and social support than to conventional disease severity. Routine psychological screening with MG-QOL-15 and SSRS may facilitate early identification of high-risk patients.